Report on COP27 and its Implications for Human Security - Marta Neškovic (Cadmus, 2023)
As a Youth Delegate of the Republic of Serbia, from the Institute for Political Studies, in Belgrade, Serbia, and a representative of the World Academy of Art and Science (WAAS), I summarize in this report the most capturing sessions I attended during the 27th Conference of the Parties to the UN Framework Convention on Climate Change (UNFCCC) – COP27, which took place in Sharm El Sheikh, Egypt, on November 6–18, 2022. This report presents the existing efforts by governments, international organizations, educational institutes and academies, and civil society organizations to address the climate change problem from the perspective of human security.